Accreditation of Prior Experiential Learning (APEL): An Alternative Entry Route to Higher Education in Malaysia - Cheng, Sheila; Siow, Heng Loke (2018)
In general, all parents, rich or poor, want their children to go to school and receive the best education they can afford. However, in reality, not all children are blessed with this opportunity for many reasons, mainly financial. Studies have revealed that educational attainment is a critical determinant of economic progress (Ariagada, 1986; Barro, n.d; Barro and Lee, 2001; Cole and Geist, 2018; Psacharopoulos and Ariagada, 1986). According to statistics from Human Resources Malaysia 2016, 20.8% of youths (15–24 years of age) and 29.2% of adults (aged 24 to 65) attained the tertiary level of education, indicating that Malaysia still has a lot of room for improve in its economic development. In order to encourage more eligible candidates to upgrade their education level and, at the same time, promote lifelong learning, the Ministry of Education Malaysia launched the APEL (Access) in 2011, as an alternative entry into tertiary education. This paper aimed to compare the academic performance in the undergraduate degree programme between the entrants admitted through APEL (A) and those who came through the standard academic admission route. Although there is extensive literature on the recognition of prior experiential learning (RPL), few researchers have looked at the relationship between entry route and academic performance, especially in Malaysia. A sample of 30 undergraduate adult learners were selected from a private institute of higher learning in Malaysia; and a comparison of their academic performance with standard route entrants in a selected semester was conducted. The study showed that there was no significant difference in the academic performance between the two groups, with adult learners performing as well as the young learners. These findings could help to build confidence in educators and policy-makers in accepting and giving a second opportunity to adult learners to pursue their educational dream.